2023
DOI: 10.3390/cancers15092537
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Malignant Transformation Differs Based on Diagnostic Criteria for Oral Lichenoid Conditions: A Systematic Review and Meta-Analysis of 24,277 Patients

Abstract: Objectives: This systematic review and meta-analysis aims to evaluate the evidence on the malignant potential of oral lichenoid conditions (OLCs) including oral lichen planus (OLP), oral lichenoid lesions (OLL), and lichenoid mucositis dysplasia (LMD). In addition, it aims to compare the rate of malignant transformation (MT) in OLP patients diagnosed according to different diagnostic criteria, and to investigate the possible risk factors for OLP MT into OSCC. Materials and methods: A standardized search strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…However, OPMDs include a number of clinically heterogeneous conditions, and the malignant transformation rates of individual diseases can vary widely (Table 2). For the OPMDs most commonly studied, the average cumulative transformation rates reported in recent systematic reviews range from 43.87% to 65.8% for PVL [37][38][39], 12.7% (19.9% in the meta-analysis) for erythroplakia [40], 7.20% to 9.8% for leukoplakia [41][42][43], 4.2% to 6% for oral submucous fibrosis [44,45], and 0.44% to 3.80% for oral lichen planus and lichenoid-type disorders [46][47][48], although the latter group is significantly influenced by the diagnostic criteria used [49], particularly the inclusion of dysplasia [50]. These estimates seem to be relatively homogeneous worldwide, including Asian countries, although there are differences reflecting regional risk factors.…”
Section: How Many Opmds Will Become Cancers?mentioning
confidence: 88%
“…However, OPMDs include a number of clinically heterogeneous conditions, and the malignant transformation rates of individual diseases can vary widely (Table 2). For the OPMDs most commonly studied, the average cumulative transformation rates reported in recent systematic reviews range from 43.87% to 65.8% for PVL [37][38][39], 12.7% (19.9% in the meta-analysis) for erythroplakia [40], 7.20% to 9.8% for leukoplakia [41][42][43], 4.2% to 6% for oral submucous fibrosis [44,45], and 0.44% to 3.80% for oral lichen planus and lichenoid-type disorders [46][47][48], although the latter group is significantly influenced by the diagnostic criteria used [49], particularly the inclusion of dysplasia [50]. These estimates seem to be relatively homogeneous worldwide, including Asian countries, although there are differences reflecting regional risk factors.…”
Section: How Many Opmds Will Become Cancers?mentioning
confidence: 88%
“…Previous prospective and retrospective studies have found a potential for malignant transformation of OLP ranging from 0.07% to 6.5% over observation periods ranging from 0.5 to 22 years [3,5,22,28]. According to WHO data, this figure varies from 0.4% to 12.5%, with an average rate of 1.09% [11,15,16,23,27,30,34,47].…”
Section: Authors' Orcid Idsmentioning
confidence: 99%
“…Therefore, OLP is a potentially malignant condition with a rate of malignant transformation ranging from 0% to 12.5% depending on the follow-up period. Studies have listed the following risk factors for the malignant transformation of OLP: lesion localization on the tongue, the red type (atrophic or erosive form), tobacco and alcohol consumption, and HCV [22,46,47]. The wide range of OLP malignant transformation rates obtained in these analyses can be attributed to differences in the diagnostic criteria used, the average follow-up periods, and the number of cases evaluated [48].…”
Section: Authors' Orcid Idsmentioning
confidence: 99%
“…In the latest published systematic review and meta-analysis, Li, J-W et al [18] examined the evidence on the MT of what they termed Oral Lichenoid Conditions (OLCs). Under this umbrella term of OLCs, the authors included OLP, OLL, and what they termed Lichenoid Mucositis Dysplasia (LMD).…”
Section: A Summary Systematic Reviewsmentioning
confidence: 99%